Abnormal Audit Profits or Costs and Factors Affecting Audit Fees - Mahmoud Lari Dashtbayaz; Zahra Rezazadeh; Toktam Safdel (Journal of Business, Communication and Technology, 2025)
Audit fees are considered important issues for the client and the auditors and a critical component of corporate governance in business environment. Abnormal audit profits or costs can signal underlying issues in audit quality, auditor independence, or financial health of the audited entity. Understanding the factors that affect audit fees is essential for stakeholders to ensure transparency and assurance in financial reporting. Effective communication between auditors and clients is crucial in addressing these issues and ensuring accurate and reliable audit outcomes. The present study examined the relationship between abnormal audit profits or costs and factors influencing audit fees. The research sample comprised 139 companies (695 firm-years) listed on the Tehran Stock Exchange (TSE) during 2016–2020. This period was selected due to significant regulatory changes and economic events that impacted audit practices and fee structures. A multiple regression model was employed to test the research hypotheses. The results showed that abnormal audit profits or costs significantly affect audit quality, Type I audit error, and audit report lag. On the other hand, abnormal audit profits or costs hurt Type II audit errors. The findings suggested that higher audit fees in Iran are more likely to represent the actual costs of conducting audits rather than excess profits. Consequently, higher audit fees lead to increased audit production costs (APC) and improved audit quality.